Temperature Effect on Optical and Electrical Properties of ZnO Films - Her, S.C.; Chi, T.C. (Asian Journal of Chemistry, 2014)
Zinc oxide thin films were deposited on a glass substrate by Radio frequency magnetron sputtering. The effect of substrate temperature on the microstructure, optical and electrical properties was investigated. Crystal structure and surface morphology of the films were examined by X-ray diffraction and atomic force microscopy. XRD patterns and AFM images show that the crystallinity and grain size are increasing with the increase of substrate temperature. Electrical properties of the films were evaluated by Hall effect measurements. Experimental results indicate a decrease of film resistivity with the increase of substrate temperature. Zinc oxide films exhibit high transmittance of 84 % in the visible wavelength range 400-800 nm and is independent on the substrate temperature. Present work shows that the enhancement of the ZnO film performance with high transparency and low resistivity can be achieved by increasing the substrate temperature.